Perceptions of women executives about symbolic violence in labor relations in the Brazilian banking sector, a challenge to human rights - Arbués, Margaret P.; Macedo , Maurides; Olmos , Andrea (Seven Editora, 2023)
This article aims to reflect on patriarchy as a product of Judeo-Christian culture that contributed to the invisibility and silencing of women throughout the historical process, transforming them into secondary labor and feeding gender discrimination by assigning them qualifying and stereotyped social roles of sinners, procreators, servants, as well as a commodity of exchange in marriage and patrimonial assets. It also discusses how the symbolic violence present in private spaces also reverberates, for public spaces, as in the work environment. It has the following problem: How is it that the power relations exercised there, even in contemporary times, are mostly presented in a discriminatory and misogynistic pattern, with women always receiving lower remuneration than men, despite the creation of laws and legal instruments protecting their work, however, almost always, ineffective? The hypothesis is that the empowerment of women with the conquest of good jobs, the advances and the mastery of new technologies with the improvement of the level of schooling or the modifications in family relations and spaces of sociability have not been enough to guarantee gender equality, since social practices persist and reaffirm such biological dichotomies between the sexes. The present research used as a methodological basis a qualitative-quantitative approach for data analysis, with the objective of knowing opinions, interests, expectations and situations experienced by women in executive positions in the banking sector, as well as analyzing their profiles (personal and professional) and their perceptions in the face of the adversities that are daily submitted. Pierre Bourdieu with the concept of symbolic violence was used as a theoretical framework, which allowed, along with the other data collected, to analyze the moral and psychological damages suffered by women bankers. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-126